Survey on the management of skin toxicity associated with EGFR inhibitors amongst French Physicians. (3rd January 2012) - Peuvrel, L; Bachmeyer, C; Reguiai, Z; Bachet, J.B.; André, T.; Bensadoun, R.J.; Bouché, O.; Ychou, M.; Dréno, B.; ,
Abstract: Background  Epidermal growth factor receptor (EGFR) inhibitors are part of the therapeutic arsenal available for advanced cancer. However, they are frequently associated with cutaneous side‐effects, which can hamper compliance, lead to treatment refusal and impair quality of life. Objective  To know the attitudes of French oncologists who deal with this skin toxicity. This work is one of the steps to build a therapeutic algorithm of side‐effects induced by EGFR inhibitors taking both evidence‐based medicine and standard practices into account. Methods  Physicians completed a questionnaire as part of regional meetings, before any discussion. Questions concerned the management of 11 clinical situations in the context of EGFR inhibitor prescription. Results  Sixty‐seven questionnaires were analysed. The collaboration with dermatologists was especially planned for persisting or worsening lesions beyond 2 weeks, but never considered at the time of the introduction of targeted therapy. The results demonstrated the difficulties encountered in diagnosing and grading skin lesions. Attitudes of oncologists were uniform for preventive care and management of mild lesions for which moisturizing and cyclines were widely prescribed. Significant differences appeared in the treatment of less typical cases such as the involvement of skin appendages, secondary infections of folliculitis or cases associated with radiodermatitis. Discrepancies existed also for what to do in relation with maintenance or interruption of EGFR inhibitor mainly if they were responsible for severe lesions. Conclusion  This original survey emphasizes the interest of greater multidisciplinary collaboration and the necessity to harmonize practice.